2016
DOI: 10.1161/circimaging.115.003557
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Echocardiography Provides Important Long-Term Prognostic Information in Selected Patients Undergoing Endovascular Abdominal Aortic Repair

Abstract: Background— The value of performing transthoracic echocardiography (TTE) as part of the clinical assessment of patients awaiting endovascular repair of the abdominal aorta is little evaluated. We aimed to estimate the prognostic importance of information derived from TTE on long-term all-cause mortality in a selected group of patients undergoing endovascular aneurysm repair. Methods and Results— This was a retrospective cohort study of 273 consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
1
15
1
Order By: Relevance
“…O'Driscoll et al. [30] showed that the self-selected hand position was 35° of extension and 7° of ulnar deviation, when testing grip strength. We have also shown in a previous study that the risk of elbow/hand disorders increase with increasing palmar flexion [31] .…”
Section: Discussionmentioning
confidence: 99%
“…O'Driscoll et al. [30] showed that the self-selected hand position was 35° of extension and 7° of ulnar deviation, when testing grip strength. We have also shown in a previous study that the risk of elbow/hand disorders increase with increasing palmar flexion [31] .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the evidence in support of additional testing to reduce intermediate and long-term morbidity and mortality is limited. In this issue of Circulation: Cardiovascular Imaging, O'Driscoll et al 10 seek to extend previous work on risk assessment by evaluating the prognostic value of transthoracic echocardiography (TTE) in patients slated for elective EVAR. Using a retrospective cohort design, the authors studied 273 consecutive patients undergoing elective EVAR between January 2008 and September 2010.…”
Section: See Article By O'driscoll Et Almentioning
confidence: 99%
“…As described by the authors, after accounting for demographics, clinical history, medications, and laboratory measures, 3 TTE indices-of 26 reported-were found to be significant predictors of long-term outcome (ie, mortality). 10 have provided informative insights into the assessment of long-term risk assessment in patients slated to undergo elective EVAR. We congratulate the authors for taking this first step into AAA risk assessment.…”
Section: See Article By O'driscoll Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…EVAR is recommended for elderly patients with aortic aneurysm as a substitute for conventional aortic grafting. However, it has been reported that cardiovascular events and deaths increase during the long-term follow-up period after EVAR 1,2 . A greater ascending aorta diameter, presence of mitral regurgitation, reduced left ventricular (LV) ejection fraction, younger age, diabetes mellitus, and the female sex were independently associated with long-term mortality after EVAR 2,3 .…”
mentioning
confidence: 99%